1988
DOI: 10.1901/jeab.1988.49-229
|View full text |Cite
|
Sign up to set email alerts
|

Information on Response Requirements Compared With Information on Food Density as a Rein Forcer of Observing in Pigeons

Abstract: On a variable-interval schedule, pecking the key to the pigeon's right (observing response) produced red or green displays relating to the delivery of grain and its dependence on pecking the key to the left (food key). During various blocks of sessions, mixed (no stimulus change) schedules including the following pairs of components were temporarily converted by the observing response to their corresponding multiple (correlated stimuli) schedules: variable-interval 60-s, extinction; variable-interval 60-s, var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
5
1
2
Order By: Relevance
“…In previous experiments, removal of the response requirement had little or no effect on the observing of pigeons (Dinsmoor, Bowe, Green, & Hanson, 1988) or baboons (Steiner, 1967). The reason for the differences between the present experiment and these previous experiments is unclear, but it is worth noting that both of the previous experiments used interval schedules of primary reinforcement.…”
Section: Discussioncontrasting
confidence: 78%
“…In previous experiments, removal of the response requirement had little or no effect on the observing of pigeons (Dinsmoor, Bowe, Green, & Hanson, 1988) or baboons (Steiner, 1967). The reason for the differences between the present experiment and these previous experiments is unclear, but it is worth noting that both of the previous experiments used interval schedules of primary reinforcement.…”
Section: Discussioncontrasting
confidence: 78%
“…Although, significantly, noncontingent schedules of reinforcement can transform temporally correlated stimuli into conditioned reinforcers (e.g., Autor, 1969;W. Baum & Rachlin, 1969;Brownstein & Pliskoff, 1968;Kelleher & Gollub, 1962;but especially Browne & Dinsmoor, 1974;Dinsmoor, Bowe, Green, & Hanson, 1988;Jenkins & Boakes, 1973), they are not effective procedures for selectively increasing the frequency of an arbitrarily chosen class of behavior.…”
Section: Absence Of Temporal Locus For Frequency Reductionmentioning
confidence: 99%
“…This general finding supports the basic conception proposed here because it shows that behavior may be reinforced by the presentation of reinforcer-correlated stimuli even when that behavior does not produce the reinforcer itself. Further, Dinsmoor, Bowe, Green, and Hanson (1988) showed that pigeons observed schedule-correlated stimuli even when the positive reinforcement schedule was a response-independent VT schedule (see also Badia, Ryan, & Harsh, 1981). These authors noted that ''the function of [observing behavior] is to bring the subject into contact with the relevant stimuli, rather than to produce the ultimate reinforcer'' (Dinsmoor et al, 1988, p. 229).…”
Section: Discussionmentioning
confidence: 99%